A buckling model for flange wrinkling in hot deep drawing aluminium alloys with macro-textured tool surfaces. (March 2017) - Zheng, Kailun; Lee, Junyi; Lin, Jianguo; Dean, Trevor A.
Abstract: The work described in this paper is the development of a buckling model based on the classical energy method of flange area material using a one-dimensional beam geometry assumption to predict flange wrinkling in hot deep drawing aluminium alloys with macro-textured blankholder surfaces. A series of deep drawing experiments utilising different macro-textured tool surfaces were performed to investigate the effects of process parameters and texture features on flange wrinkling. The results have shown that wrinkling occurs when the hollow dimension of radially grooved textures reached a certain magnitude dependent on process conditions. A dislocation-driven based continuum damage mechanism (CDM) material model for aluminium alloys at elevated temperatures was used to model the viscoplastic behaviour during deformation. The newly developed buckling model was validated by comparison with experimental results. The predicted results showed that the resistance to wrinkling increases with increasing forming temperature and decreasing forming speed, depending on the particular viscoplastic characteristics of the work-piece. The effects of texture ratio and draw ratio on wrinkling were found to be more significant than the effects of the temperature and strain rate. The buckling model developed in this paper can be used to model the flange wrinkling phenomena, as well as the non-isothermal feature in the hot stamping condition using the macro-textured tool surfaces. Highlights: A flange buckling model for hot forming AA6082 with textured tools were developed. The non-isothermal feature of hot stamping process was modelled. Hot deep drawing were performed to validate the developed buckling model. Effects of process parameters and tool textures on wrinkling were analysed.